Innovation of public service delivery: Zero-Pendency and Daily Disposal (ZPDD) initiative in Pune collectorate - Mulla, Zubin R.; Saini, Gordhan K. (2013)
A unique initiative was undertaken by Pune collectorate called, "Zero Pendency and Daily Disposal" (ZPDD). The initiative, was aimed to streamline all the processes in the offices of Pune collectorate with a view to bring in transparency in the system and to enhance service quality for the citizens. In this study, the responses of the citizens to the service provided by offices of the Pune Collector at various places in Pune district were measured. Two hundred fifty one citizens were interviewed using a validated questionnaire and open-ended interviews to understand their experiences with the service of Pune Collectorate. Citizens are quite satisfied with the services provided and while they have observed a significant improvement in service quality after the initiative, the actual performance in terms of adherence to promised timings of delivery remains poor. Overall, the citizens and employees were happy with the improvements due to the ZPDD initiative. - Reproduced.
Keywords: Public utilities